Auricular Point Acupressure to Manage Chronic Low Back Pain in Older Adults: A Randomized Controlled Pilot Study. (24th July 2014) - Yeh, Chao Hsing; Morone, Natalia E.; Chien, Lung-Chang; Cao, Yuling; Lu, Huijuan; Shen, Juan; Margolis, Leah; Bhatnagar, Shreya; Hoffman, Samuel; Liang, Zhan; Glick, Ronald M.; Suen, Lorna Kwai-Ping
Abstract : This prospective, randomized clinical trial (RCT) pilot study was designed to (1) assess the feasibility and tolerability of an easily administered, auricular point acupressure (APA) intervention and (2) provide an initial assessment of effect size as compared to a sham treatment. Thirty-seven subjects were randomized to receive either the real or sham APA treatment. All participants were treated once a week for 4 weeks. Self-report measures were obtained at baseline, weekly during treatment, at end-of-intervention (EOI), and at a 1-month follow-up. A dropout rate of 26% in the real APA group and 50% in the sham group was observed. The reduction in worst pain from baseline to EOI was 41% for the real and 5% for the sham group with a Cohen's effect size of 1.22 P < 0.00 . Disability scores on the Roland Morris Disability Questionnaire (RMDQ) decreased in the real group by 29% and were unchanged in the sham group (+3%) P < 0.00 . Given the high dropout rate, results must be interpreted with caution; nevertheless, our results suggest that APA may provide an inexpensive and effective complementary approach for the management of back pain in older adults, and further study is warranted.